Participatory Approach on Water Scarcity Solutions in Pranburi Basin, Thailand - NOIMUNWA, Watcharapong; SINGHRUCK, Patama; SOMPONGCHAIYAKUL, Penjai (Journal of Environmental Management and Tourism; Vol 8 No 7 (2017): JEMT Volume VIII Issue 7(23) Winter 2017, 2018)
Water scarcity is the main problems of water management and various socio-economic development activities of Thailand. Expert opinion and scientific knowledge are always convenient to be used to solve problems. To some extent, this approach may not be applicable since it is not accepted by local communities. To reduce this conflict, participatory approach may provide local cooperation and assist developing better water management strategies. Pranburi Basin is an important headwater that supports both agricultural land and municipality which includes Hua-Hin, a famous tourist place. The aims of this study were to assess water scarcity and to apply stakeholder participation into decision making processes for water management. Water stress index and criticality ratio were used to assess water scarcity. A Driver-Pressure-State-Impact-Response (DPSIR) framework was used to describe water scarcity and contributing factors. Based on DPSIR analysis, the stakeholders proposed and then prioritized for the most appropriate responses by ordinary weighing technique. The results indicated that the four most preferable measures for this basin include controlling agricultural area, controlling crop types, reforestation and establishing local water user association.